Prebiotic potential of Polysaccharides extracted from Gigantochloa Levis (Buluh Beting) shoots / Prof. Madya Dr. Shuhaimi Mustafa … [et al.] - Mustafa, Shuhaimi; Muhammad Nurul Azmi, Aida Firdaus; Mat Hashim, Dzulkifly; Abd Manap, Mohd Yazid (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Recently, there is an increasing trend of consumer awareness towards the demand for functional foods. Apart from other food ingredients, prebiotics are among those which have attracted much attention. Bamboo shoot crude polysaccharides (BSCP) extracted from the shoots of Gigantochloa Levis gave about 3.27+ 0.18% on dry basis. The molecular weight of BSCP estimated by gel chromatography was found to be around 7.49 x 103 Da, while the molecular weights of purified fractions (Fl to F5) were around 1550.96, extract could contains p-glucan, which can be considered a valuable compound for the medical and food industries. These relate to the resistance of BSCP towards artificial human gastric juice which is more than 99%. Prebiotic activity tested using BSCP as a carbon source showed significant increase in the growth of B. animalis ATCC 1053, B. longum BB 536 and L. acidophilus ATCC 4356 as compared to FOS. Survivability of S. choleraesuis JCM 6977 was found to be slower in both BSCP and FOS. Study conducted reflects a good sign for the BSCP to be exploited as a promising prebiotic.